The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1126/science.6879176
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Dopaminergic Involvement in Cocaine Reinforcement

Abstract: Neuronal systems involved in the initiation of cocaine reinforcement were investigated by identifying brain sites where direct application of the drug was reinforcing. This was accomplished by allowing rats to self-administer picomolar concentrations of cocaine into discrete brain regions. The medial prefrontal cortex supported self-administration, while the nucleus accumbens and ventral tegmental area did not. Self-administration could be attenuated by including equimolar concentrations of the dopaminergic D2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
172
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(181 citation statements)
references
References 17 publications
8
172
1
Order By: Relevance
“…The current data also fail to provide simple correlations with models that postulate that enhanced PFc DA levels are necessary and sufficient for cocaine reward. This hypothesis has also been supported by a substantial body of lesion and microinjection data (Goeders and Smith, 1983;Goeders et al, 1986;Bardo, 1998;Tzschentke, 2001). Cocaine increases DA ex in PFc of both wild-type and homozygous DAT-KO mice that exhibit cocaine reward and DAT/SERT double homozygous KO mice that do not display cocaine reward.…”
Section: Differential Da Responses In To Cocaine In Cpu Nac and Pfcmentioning
confidence: 74%
“…The current data also fail to provide simple correlations with models that postulate that enhanced PFc DA levels are necessary and sufficient for cocaine reward. This hypothesis has also been supported by a substantial body of lesion and microinjection data (Goeders and Smith, 1983;Goeders et al, 1986;Bardo, 1998;Tzschentke, 2001). Cocaine increases DA ex in PFc of both wild-type and homozygous DAT-KO mice that exhibit cocaine reward and DAT/SERT double homozygous KO mice that do not display cocaine reward.…”
Section: Differential Da Responses In To Cocaine In Cpu Nac and Pfcmentioning
confidence: 74%
“…ICV CRH has little or no effect on dopamine in the nucleus accumbens (Kalivas et al 1987;Dunn and Berridge 1990) and actually increases dopamine metabolism in the medial prefrontal cortex (Dunn and Berridge 1990). Nevertheless, in consideration of the putative dual role for the medial prefrontal cortex in the neurobiological response to stress as well as in the initiation of cocaine-seeking behavior (Goeders and Smith 1983;Goeders 1997), it is likely that CRHinduced alterations in dopaminergic neurotransmission play an important role in this peptide's effects on cocaine responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Self-administration studies have identi®ed cocaine as an extremely powerful reinforcer. Additionally, a substantial body of evidence has linked cocaine's reinforcing properties to its ability to increase dopaminergic neurotransmission within the mesocorticolimbic circuit (Goeders and Smith, 1983). Studies with dopamine receptor agonists and antagonists have demonstrated involvement of both D 1 and D 2 dopamine receptor subtypes in the acute reinforcing effects of cocaine (Bergman et al, 1990).…”
Section: Receptors Mediate Cocaine-induced Behaviorsmentioning
confidence: 99%